"Sign in Lucy" Movie Script by Luc Besson : Semiotics Approach by Charles Sanders Pierce - Chayrul Hidayat (ELITE: Journal of English Language and Literature, 2020)
This research aims at describing the meaning of sign at the object in Lucy movie script by Luc Besson. This research focuses on what is the meaning of icon, index, and symbol in Lucy's movie script by Luc Besson. This research applies the qualitative method. The primary data in this research is acquired from the Lucy movie script written by Luc Besson and the secondary data from the Lucy movie directed by Luc Besson. The theory of Charles Sanders Pierce is used to uncover the sign on the object itself which consists of an icon, index, and symbol to define the meaning of the sign itself in the material object. The finding reveals that three kinds of signs are found in the movie script including icon, index, and symbol. The result of this research from the data shows that there are three kinds of signs found in Lucy's movie script, and the researcher found 18 data which consist of33 signs, namely: 14 icons, 13 indexes, and 6 symbols. The meaning of the icon, index, and symbol found in Lucy's movie script is about the drug packages themselves that called CPH4 and how it affects Lucy and the distribution of CPH4 from Richard until to the people who are forced to work by Mr. Wang, one of them is Lucy. Then, Lucy struggles to get all the CPH4 to save her life because of the harmful effects of the drugs that threatened her life.